Network Crosstalk as a Basis for Drug Repurposing - Guala, Dimitri; Sonnhammer, Erik L. L. (Frontiers in Genetics, 2022)
The need for systematic drug repurposing has seen a steady increase over the past decade, and may be particularly valuable to quickly remedy unexpected pandemics. The abundance of functional interaction data has allowed mapping of substantial parts of the human interactome modeled using functional association networks, favouring network-based drug repurposing. Network crosstalk-based approaches have never been tested for drug repurposing despite their success in the related and more mature field of pathway enrichment analysis. We have therefore evaluated the top performing crosstalk-based approaches for drug repurposing. Additionally, the volume of new interaction data as well as more sophisticated network integration approaches compelled us to construct a new benchmark for performance assessment of network-based drug repurposing tools, which we used to compare network crosstalk-based methods with a state-of-the-art technique. We found that network crosstalk-based drug repurposing is able to rival the state-of-the-art method and in some cases outperform it.